Quest for regional integration in the East African community - Drummond, Paulo Flavio Nacif, 1966-; Wajid, Syed Khalid S.; Williams, Oral.; International Monetary Fund. ([Washington, D.C.] : International Monetary Fund, 2014)
The countries in the East African Community (EAC) are among the fastest growing economies in sub-Saharan Africa. The EAC countries are making significant progress toward financial integration, including harmonization of supervisory arrangements and practices and the modernization of monetary policy frameworks. This book focuses on regional integration in the EAC and argues that the establishment of a time table for the eliminating the sensitive-Products list and establishing a supranational legal framework for resolving trade disputes are important reforms that should foster regional integration.
Sustaining growth in the East African community / Catherine McAuliffe, Sweta C. Saxena, and Masafumi Yabara -- Economic convergence to support the East African monetary union / Nabil Ben Ltaifa, Masafumi Yabara, and Oral Williams -- The fiscal policy challenges of monetary union in East Africa / Sanjeev Gupta and Jimmy McHugh -- Implications of monetary union for national fiscal institutions in East Africa / Richard Hughes -- Building a framework to harmonize monetary policy / Armando Morales -- How strong is the monetary transmission mechanism in the East African Community? / Hamid R. Davoodi, Shiv Dixit, and Gabor Pinter -- Exchange rate arrangements in the transition to East African monetary union / Christopher S. Adam ... [et al.] -- Financial sector stability: a regional approach / Mary Zephirin and S. Kal Wajid -- Cross-country financial linkages and implications for financial sector supervision / Etibar Jafarov -- Financial integration ahead of East African monetary union / Masafumi Yabara -- Themes and lessons from the financial sector assessment program / S. Kal Wajid.
Includes bibliographical references and index.
Keywords: East African Community; East African Community; Monetary unions -- Africa, Eastern; Fiscal policy -- Africa, Eastern; Monetary policy -- Africa, Eastern; Economic development -- Africa, Eastern; Financial risk management -- Africa, Eastern; Economic development; Economic policy; Financial risk management; Fiscal policy; International economic integration; International economic relations; Monetary policy; Monetary unions; Africa, Eastern -- Economic integration; Africa, Eastern -- Economic policy; Africa, Eastern -- Foreign economic relations; Africa, Eastern; Electronic books